Molecular Diagnostic Yield of Exome Sequencing in Patients With Cerebral Palsy. Issue 7 (July 2021) - Moreno-De-Luca, Andrés; Millan, Francisca; Pesacreta, Denis R.; Elloumi, Houda Z.; Oetjens, Matthew T.; Teigen, Claire; Wain, Karen E.; Scuffins, Julie; Myers, Scott M.; Torene, Rebecca I.; Gainullin, Vladimir G.; Arvai, Kevin; et al.
Abstract : (Abstracted from JAMA 2021;325:467–475) Cerebral palsy (CP) is a nonprogressive neurodevelopmental disorder that affects early motor development and typically impairs movement and posture. The adult population with CP is increasing as the life expectancy increases with changes in medical and social care.